Can Human Rights and Indigenous Spirituality Prevail over State-Corporatism? A Narrative of Ecological and Cultural Rights Violation from East Kalimantan, Indonesia - Mirza Satria Buana (Jember University Press, 2017)
This article examines both theoretical and empirical discussion on strategies to overcome state-corporatism and developmentalism practices in East Kalimantan, Indonesia. State-corporatism is the term used to describe a political condition when a state has a strong linkage to organized groups. Developmentalism is an over-arching concept to describe a strong tendency of a state to maximize economics growths through investment, while disregarding people’s fundamental rights. East Kalimantan Province is selected because it is highly known as one of the enournous amount of natural resources found within among other provinces in Indonesia. However, the richness of this province has become a curse of its people due to massive destructions of natural resources. This paper seeks to analyse in what way human rights’ principles and indigenous spirituality can lessen the negative effects of ‘development’ projects sustained by state-corporatism. This article contemplates what strategies that can be executed to diminish state-corporatism effects in East Kalimantan, particularly in two important districts: Regency of Kutai Kartanegara and Bontang Municipality. This article argues that the indigenous spirituality is a key to battle state-corporatism’s influences. Indigenous spirituality as forum internum is still a potential tool of advocacy. By capitalizing the role of shamans, indigenous peoples might still have opportunities to reclaim and defend their cultural rights.